Transmissão da malária residual de sistemas de Mata Atlântica no Espírito Santo : comportamento vetorial e caracterização molecular das espécies de Plasmodium circulantes - Buery, Julyana Cerqueira (2018)
In the Southern and Southeastern regions of Brazil, autochtonous malaria cases can be found close to the Atlantic Forest fragments. In Espírito Santo state, this disease is particularly frequent, and Plasmodium vivax is the parasite commonly recognized as the etiological agent of human infections. However, when spatial and temporal distances between the reported cases and the behavior of local insect vectors, especially the Anopheles (Kerteszia) cruzii, are observed the transmission cycle does not correspond to the traditional cycle of malaria. Thus, the hypothesis of the existence of a zoonosis, with infected simians maintaining the transmission, was established. Considering that there are obscure aspects regarding bromeliad-malaria, as it is called, the evaluation of the components of the transmission cycle is necessary. In the present study, the transmission of bromeliad-malaria in the rural endemic region of Espírito Santo is investigated based on two main pillars: behavioral analysis of the Anopheles vectors, mainly those of the subgenus Kerteszia, and comparison of the complete mitochondrial genome from several isolates of Plasmodium spp. The isolates were infecting humans, simians of the genus Allouata and mosquitoes Anopheles spp. from the same region. Light CO2 traps (CDC-CO2) were installed in open areas, inside the forest and at its edge, and Shannon traps were installed on the edge of the forest. The mitochondrial genome of Plasmodium spp. found in the different hosts was completely sequenced and compared in a haplotype network that included all sequences of P. vivax/simian mitochondrial genomes from samples from humans and simians from other regions of Brazil. A total of 1,414 anophelines were captured from 13 species. Anopheles (Kerteszia) cruzii DyarΛ continued to be the more captured species in the forest canopy and was also the vector with the highest prevalence of Plasmodium vivax infection according to molecular PCR techniques. The haplotype network indicated that humans and simians of the Atlantic Forest were infected by the same haplotype, but some isolates of humans are not identical to the simian isolate. In addition, DNA of Plasmodium spp. extracted from mosquitoes presented sequences different from those obtained from simians, but similar to those retrieved from two isolates from humans. This study revealed that the acrodendrophilic behavior of vectors, especially those infected, reinforces the hypothesis that the presence of P. vivax in these specimens arises from the blood of animals that live in the top of the trees, such as monkeys. The comparison of the mitochondrial genomes of the parasites shows that, in the Atlantic Forest, especially in Espírito Santo, parasites with similar molecular structures are shared by humans and simians. The recognized identity between P. vivax and P. simium, the shared haplotypes, and the participation of the same vector in the transmission of the infection to both host species indicates interspecies transfer of the parasites.